2020
DOI: 10.24965/gapp.i23.10641
|View full text |Cite
|
Sign up to set email alerts
|

New Governance Mechanisms Contributing to the Integration of National Climate Change Adaptation and Mitigation Policies in the Brazilian Amazon

Abstract: Research in the field of Global Environmental Governance (GEG) pays considerable attention to the emergence of New Governance Mechanisms (NGM). NGM poses profound challenges to governments and institutions in the Developed and Developing world alike, corresponding to new ways of participation. This article seeks to contribute to the debates on NGM by analyzing a municipal-level environmental governance scheme based on deforestation-free commitments emerged in 2011, in Brazil, that has successfully helped to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“… Ferreira, C. G. et al. (2020) 22 New Governance Mechanisms Contributing to the Integration of National Climate Change Adaptation and Mitigation Policies in the Brazilian Amazon Brazil Government Analyse a municipal-level environmental governance scheme based on deforestation-free commitments in Brazil. These strategies have been successful in reducing deforestation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… Ferreira, C. G. et al. (2020) 22 New Governance Mechanisms Contributing to the Integration of National Climate Change Adaptation and Mitigation Policies in the Brazilian Amazon Brazil Government Analyse a municipal-level environmental governance scheme based on deforestation-free commitments in Brazil. These strategies have been successful in reducing deforestation.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies examined local governance at the municipal level. First, Ferreira 22 analysed the municipal-level environmental governance scheme called the Green Municipalities Program (PMV, by its Portuguese acronym) which was started in Brazil in 2011 in an effort to reduce deforestation. The study reported that while the PMV showed excellent results in bringing together different partners, matching multi-level policies, and promoting decentralisation, with effective political coordination and articulation among stakeholders; many aspects of this governance mechanism still rely on old national economic strategies, particularly to meet market pressures to maintain the exportation of raw materials.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Donde Lefont et al (2020) precisan que es el diseño de planes y convenios en base a los problemas que acontecen en la sociedad, y que buscan tener un impacto significativo y relevante en la población. En cuanto a la gobernabilidad, Ferreira (2020) infiere que la gobernabilidad es el escenario en donde se presentan una serie de circunstancias propicias para el accionar del gobierno, las cuales permiten que se pueda desarrollar una buena capacidad de gobernanza de tal manera que se alcance un óptimo nivel de desarrollo. De igual manera, Munir et al (2020) es la manera en la que las instituciones estatales ejercen su poder de manera adecuada y transparente con el propósito de proponer medidas estratégicas y asertivas frente a los problemas que susciten en la población.…”
Section: Bases Teóricas De La Investigaciónunclassified
“…Creating the right conditions for policymakers and civil society actors is crucial, notably securing food for disadvantaged and exposed populations (Santarelli et al, 2018). Such conditions must be articulated so as not to interfere or to worsen a fragile balance, which is often difficult to reconcile in an economic, fiscal, environmental, and sociopolitical setting that favors large agribusiness groups and corporations in detriment of small farmers and traditional communities (Guanziroli & Basco, 2010;Bateman et al, 2013;Paulino, 2014;Mayer, 2016;Santos & Freitas, 2017;Santarelli et al, 2018;Sauer et al, 2018;Ferreira Costa, 2020b).…”
Section: The Food and Nutrition Security (Fns) Versus The Fiscal Agenda In Brazil: A Dynamic Processmentioning
confidence: 99%